eNOS Deficiency Acts through Endothelin to Aggravate sFlt-1–Induced Pre-Eclampsia–Like Phenotype - Li, Feng (American Society of Nephrology, 2012)
Excess soluble fms-like tyrosine kinase 1 (sFlt-1) of vascular endothelial growth factor receptor 1 secreted from the placenta causes pre-eclampsia–like features by antagonizing vascular endothelial growth factor signaling, which can lead to reduced endothelial nitric oxide synthase (eNOS) activity; the effect of this concomitant decrease in eNOS activity is unknown. We tested whether the decrease in nitric oxide occurring in female mice lacking eNOS aggravates the pre-eclampsia–like phenotype induced by increased sFlt-1. Untreated eNOS-deficient female mice had higher BP than wild-type mice. Adenovirus-mediated overexpression of sFlt-1 increased systolic BP by approximately 27 mmHg and led to severe loss of fenestration of glomerular capillary endothelial cells in both eNOS-deficient and wild-type mice. However, only the eNOS-deficient sFlt-1 mice exhibited severe foot process effacement. Compared with wild-type sFlt-1 mice, eNOS-deficient sFlt-1 mice also showed markedly higher urinary albumin excretion (467±74 versus 174±23 μg/d), lower creatinine clearance (126±29 versus 452±63 μl/min), and more severe endotheliosis. Expression of preproendothelin-1 (ET-1) and its ET(A) receptor in the kidney was higher in eNOS-deficient sFlt-1 mice than in wild-type sFlt-1 mice. Furthermore, the selective ET(A) receptor antagonist ambrisentan attenuated the increases in BP and urinary albumin excretion and ameliorated endotheliosis in both wild-type and eNOS-deficient sFlt-1 mice. Ambrisentan improved creatinine clearance and podocyte effacement in eNOS-deficient sFlt-1 mice. In conclusion, reduced maternal eNOS/nitric oxide exacerbates the sFlt1-related pre-eclampsia–like phenotype through activation of the endothelin system.